2019
DOI: 10.1111/febs.14741
|View full text |Cite
|
Sign up to set email alerts
|

Structural, thermodynamic and catalytic characterization of an ancestral triosephosphate isomerase reveal early evolutionary coupling between monomer association and function

Abstract: Function, structure, and stability are strongly coupled in obligated oligomers, such as triosephosphate isomerase (TIM). However, little is known about how this coupling evolved. To address this question, five ancestral TIMs (ancTIMs) in the opisthokont lineage were inferred. The encoded proteins were purified and characterized, and spectroscopic and hydrodynamic analysis indicated that all are folded dimers. The catalytic efficiency of ancTIMs is very high and all dissociate into inactive and partially unfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Following from this, elastic network models have also shown that TIM-barrel proteins with conserved structure but without functional conservation can also have greatly different intrinsic dynamics tying in with their functional differences [77]. This is not a recent evolutionary event in TIM development, as studies of ancestral TIMs obtained through ancestral inference have indicated the presence of early evolutionary coupling between oligomerization and function [78]. Finally, mutagenesis studies of TIMs from the protozoan parasite Trichomonas vagina ( Tv TIM) that are capable of dissociating into stable monomers, but that dimerize once substrate binds, have shown that the dimerization is necessary for assembly of a catalytically competent active site, but that as it is being assembled, the active site itself acts to stabilize the dimer [79].…”
Section: Loop Motion and Dimer Assembly In Triosephosphate Isomerasementioning
confidence: 99%
“…Following from this, elastic network models have also shown that TIM-barrel proteins with conserved structure but without functional conservation can also have greatly different intrinsic dynamics tying in with their functional differences [77]. This is not a recent evolutionary event in TIM development, as studies of ancestral TIMs obtained through ancestral inference have indicated the presence of early evolutionary coupling between oligomerization and function [78]. Finally, mutagenesis studies of TIMs from the protozoan parasite Trichomonas vagina ( Tv TIM) that are capable of dissociating into stable monomers, but that dimerize once substrate binds, have shown that the dimerization is necessary for assembly of a catalytically competent active site, but that as it is being assembled, the active site itself acts to stabilize the dimer [79].…”
Section: Loop Motion and Dimer Assembly In Triosephosphate Isomerasementioning
confidence: 99%
“…The predicted and annotated sequence of FoxTPI was used to perform a BLAST protein data bank (PDB) using a target database of 3D structures. The homology model of the full-length FoxTPI enzyme was built on the Swiss-Model server [35] using the crystallographic structure of the TPI from Eukaryotes (TIM63; PDB entry 6NEE; sequence identity: 68.5%) [36] as a template for calculations. The best model was selected according to the global model quality estimation (GMQE), quaternary structure quality estimate (QSQE), and qualitative model energy analysis (QMEAN) statistical parameters and subjected to energy minimization using the YASARA software [37].…”
Section: Bioinformatics and Homology Modeling Of Foxtpimentioning
confidence: 99%
“…According to a BlastP against Protein Data Bank (PDB), the FoxTPI sequence has an identity of 68.5% with TIM63 (PDB entry 6NEE; [36]), 60.4% with the TPI from Arabidopsis thaliana (PDB entry 4OBT; [51]) and 57.8% with Opisthorchis viverrini (PDB entry 5ZG4; [60]. Thus, the crystal structure of TIM63 was used to generate the FoxTPI model using the Swiss-Model server [39].…”
Section: Homology Modeling Of the Foxtpi Proteinmentioning
confidence: 99%
“…Our next article also looks at molecular biology in the light of evolution: In their Editor’s Choice research article [2], Daniel Alejandro Fernández‐Velasco and colleagues focus on triosephosphate isomerases (TIMs), ubiquitous glycolytic homo‐oligomeric enzymes, and use five opisthokontal TIMs identified by ancestral sequence reconstruction (ASR) to compare them with extant TIMs in their structural and biochemical analyses. The authors find that the ancestral TIMs were folded dimers and their dissociation leads to structured, but inactive monomers.…”
mentioning
confidence: 99%
“…Our next article also looks at molecular biology in the light of evolution: In their Editor's Choice research article [2], Daniel Alejandro Fern andez-Velasco and colleagues focus on triosephosphate Abbreviations ER, endoplasmic reticulum; Ero1, ER oxidoreductase; H2S, Hydrogen Sulfide; Kgb, Kumaglobin; PDI, Protein Disulfide Isomerase; redox, reduction-oxidation; TIMs, triosephosphate isomerases. isomerases (TIMs), ubiquitous glycolytic homooligomeric enzymes, and use five opisthokontal TIMs identified by ancestral sequence reconstruction (ASR) to compare them with extant TIMs in their structural and biochemical analyses.…”
mentioning
confidence: 99%